Exploring initiation schools' impact on HIV and AIDS management in the Vhembe district of South Africa: An ethnography - Avhatakali A. Ndou-Mammbona (AOSIS, 2023)
Background: This article presents the positive and negative impact traditional initiation schools have on the management of HIV and AIDS in the Vhembe district in South Africa. Aim: To explore the impact of initiation schools regarding the management of HIV and AIDS. Setting: This ethnographic study was conducted in rural villages in the Vhembe district. Methods: Nine purposively sampled key informants from the Vhavenda traditional healers and leaders participated in the study. Data were collected using semi-structured face-to-face interviews guided by an interview and observation guide. Data were analysed using ethnographic content analysis. Results: The results indicated that the Vhavenda have different traditional initiation schools for boys and girls. For boys, there is Muḽa [traditional male circumcision], while Musevhetho [first stage of girls' traditional initiation before puberty], Vhusha [girls' second stage of traditional initiation] and Domba [final stage of girls' traditional initiation] are for girls. Some of the information provided perpetuates engagement in multiple concurrent relationships predisposing them to contract HIV. Boys are encouraged to be strong and to control women when it comes to sexual activities to suit their desire, whether the woman consented or not, while girls are taught to be submissive to their husbands which can fuel the spread of HIV. Conclusion: As the initiates are attentive to whatever is said during those initiation schools, there is an opportunity for using these initiation schools for proper prevention of HIV and instilling positive behaviours by using Leininger's cultural care modalities which focus on preservation of beneficial practices and repatterning of practices which fuel the spread of HIV. Contribution: The study findings will aid in the review and update of the manuals and procedures for HIV and AIDS management.